DESIGN OF PREPARATION OF FINANCIAL STATEMENTS BASED ON SAK EMKM IN WAK MENOK BANANA CHIPS MSMEs IN LAMONGAN - Sholawati, Richma Sholawati Richma; Octaviana, Ulfi Kartika (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 9 No 1 (2023): The 9th International Conference of Islamic Economics and Business (ICONIES 2023), 2023)
In Indonesia, the applicable accounting standards are based on SAK-EMKM. The purpose of making financial reports can help Wak Menok find out the amount of assets, equity, liabilities and assets owned, as well as the net profit earned. Financial reports can also help Wak Menok MSMEs make decisions for the next steps. The researcher chose a descriptive qualitative approach, using interview, observation, and documentation data collection techniques. Researchers designed the preparation of financial reports using Microsoft assistance, which consisted of: statements of financial position, income statements and notes to financial statements (CALK). In the financial reports prepared by the researchers for the January 2023 period, profit and loss after tax of Rp. 3,113,501 total liabilities and equity in the statement of financial position amounted.